Left Atrial Diameter Index Predicts Cerebrovascular Events After POAF Following CABG - Doğan, Arda Can; demir, ali rıza; Ateşli Yazıcı, Alkım; Yazıcı, Batuhan; Kalkan, Ali Kemal (The Thoracic and Cardiovascular Surgeon)
ABSTRACT Objective: Postoperative atrial fibrillation (POAF) is a frequent complication after coronary artery bypass grafting (CABG) and is linked to increased short- and long-term stroke risk. This study evaluated the prognostic value of the left atrial diameter index (LADI) for predicting cerebrovascular events (CVE) in patients undergoing isolated CABG who developed POAF, had no prior atrial fibrillation (AF), and were discharged in sinus rhythm. Materials and Methods: Among 2094 patients undergoing isolated CABG between June 2015 and June 2022, 392 consecutive patients with POAF and discharge in sinus rhythm met inclusion criteria. LADI was calculated preoperatively, and an optimal cutoff (21.2 mm/m²) was determined via receiver operating characteristic (ROC) curve and Youden index. Patients were classified as low (≤21.2 mm/m²) or high (>21.2 mm/m²) LADI. The association between LADI and CVE was assessed over a mean follow-up of 42.4±20.0 months using Cox proportional hazards modeling. Results: Thirty patients (7.7%) experienced a CVE, including 8 in-hospital cases (2.0%). CVE incidence was higher in the high LADI group compared to the low LADI group (19.8% vs. 2.8%). Multivariable analysis identified older age, hypertension, congestive heart failure, and high LADI as independent CVE predictors. Kaplan-Meier analysis confirmed significantly higher CVE rates in the high LADI group (log-rank p<0.001). Conclusion: In patients developing POAF after isolated CABG, LADI is a simple, easily obtainable parameter that independently predicts long-term CVE risk and may aid in postoperative risk stratification.